Pengaruh Konsumsi Jamu Kunyit Asam Terhadap Penurunan Nyeri Dismenore Primer pada Remaja Putri - Ridwan, M.; Fibrila, Firda; Herlina (Melati Institute, 2024)
Primary dysmenorrhea is menstrual pain without reproductive organ abnormalities or gynecological disorders. Data shows that 90% of Indonesian women have experienced dysmenorrhea and almost all of them do not go to health services. The prevalence rate of dysmenorrhea in Indonesia according to the Occupational Environmental Journal is primary dysmenorrhea (54, 98%) and secondary dysmenorrhea (9.36%). The cause is excessive amounts of prostaglandins in menstrual blood which stimulates uterine hyperactivity. The results of interviews conducted in March 2024 with first year students showed that out of 87 female students, 53 students (66.25%) experienced dysmenorrhea during menstruation. This study aims to determine the effect of consuming tamarind turmeric herbal medicine on reducing dysmenorrhea in adolescent girls in the Metro Midwifery Study Program in 2024. This type of research is quasi-experimental. The research population was 53 students from the Metro Midwifery Study Program level I in 2024. The sample was determined using the minimum sample size formula (Lemeshow, 1997) so that a sample of 21 intervention and control groups each was obtained, using the purposive sampling method. How to collect data using a questionnaire. Data analysis used univariate and bivariate analysis using the dependent T-test parametric statistical test. The research results showed that the average pain intensity in the intervention group before the study was 5.43. The average pain intensity in the control group before the study was 5.10. The average pain intensity in the intervention group after the study was reduced to 2.38 with a p value of 0.000. The average pain intensity in the control group after the research was carried out increased to 5.48 with a p value of 0.119. The conclusion is that there is an influence of consumption of tamarind turmeric herbal medicine on reducing dysmenorrhea in young women in the Metro Midwifery Study Program in 2014. Suggestions for students can be to make tamarind turmeric herbal medicine a safe and effective alternative in treating primary dysmenorrhea by drinking it two days before menstruation for up to two days during menstruation in every cycle.